Slope stability analysis of riverbank in Malaysia with the effects of vegetation - Razali, Irfan Haziq; Mohd Taib, Aizat; Abd Rahman, Norinah; Abang Hasbollah, Dayang Zulaika; Md Dan, Mohd Firdaus; Ramli, Ahmad Bukhari; Ibrahim, Aniza (Elsevier, 2023)
Malaysia has experienced several slope failures in the past and vegetation is one of the solutions that can help to increase the stability of slopes by preventing erosion and providing interlocking forces in the soil materials. This study investigates the effect of vegetation on riverbank slope stability in Malaysia. The analysis was conducted to capture the pattern of changes in terms of the factor of safety (FOS) of slopes. Using Plaxis, a total of 24 models were constructed consisting of two methods of modelling namely node-to-node anchor and geotextile, which act as vegetation. The modelling results show that the slope safety factor changed according to the addition of vegetation to the slope. The existing slope conditions recorded a safety factor at the value of 2.97. The value then increased when plants were added by adopting the node-to-node anchor along the top of the soil with the highest factor of safety value of 2.99. On the other hand, the factor of safety of slopes with the application of geotextile also shows an increase of up to 3.185. Whereas for the slopes with the effect of rainfall, the factor of safety values dropped to 2.609 and increase to 2.96 when vegetation was applied. This study indicates that vegetation canimprove slope stability and that the different types of roots can also affect slope behaviour.